Association of Self-Reported Aerobic Physical Activity, Muscle-Strengthening Physical Activity, and Stretching Behavior With Presenteeism. Issue 5 (May 2017) - Walker, Timothy J.; Tullar, Jessica M.; Diamond, Pamela M.; Kohl, Harold W.; Amick, Benjamin C.
Abstract : Objective: The aim of this study was to evaluate relations between aerobic physical activity (PA), muscle-strengthening PA, and stretching behavior and presenteeism in university employees. Methods: A cross-sectional study used health assessment data from two employee respondent groups ( n 2015  = 10, 791 and n 2009  = 10, 165). Multivariable zero-inflated negative binomial regression models assessed the association between self-reported PA types and presenteeism. Results: There was consistent evidence that employees who reported participating in sufficient aerobic PA had higher odds for no work limitations [odds ratio (OR2015 ) = 1.45, P  < 0.001; OR2009  = 1.55, P  < 0.001] and lower levels of work limitations [incidence rate ratio (IRR)2015  = 0.92, P  < 0.05; IRR2009  = 0.83, P  < 0.001] than employees who reported participating in no activity. There was some evidence of an inverse association between muscle-strengthening PA and work limitations, but no evidence between stretching behavior and work limitations. Conclusions: Promoting PA among employees is a key health behavior to target for worksites concerned about presenteeism.